Cysteine proteases as therapeutic targets: does selectivity matter? A systematic review of calpain and cathepsin inhibitors - Marton Siklos; Manel BenAissa; Gregory R.J. Thatcher (Elsevier, 2015)
Cysteine proteases continue to provide validated targets for treatment of human diseases. In neurodegenerative disorders, multiple cysteine proteases provide targets for enzyme inhibitors, notably caspases, calpains, and cathepsins. The reactive, active-site cysteine provides specificity for many inhibitor designs over other families of proteases, such as aspartate and serine; however, a) inhibitor strategies often use covalent enzyme modification, and b) obtaining selectivity within families of cysteine proteases and their isozymes is problematic. This review provides a general update on strategies for cysteine protease inhibitor design and a focus on cathepsin B and calpain 1 as drug targets for neurodegenerative disorders; the latter focus providing an interesting query for the contemporary assumptions that irreversible, covalent protein modification and low selectivity are anathema to therapeutic safety and efficacy.